2002
DOI: 10.1139/z02-059
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elk group size on predation by wolves

Abstract: Wolf-prey research has focused on single-prey systems in North America dominated by moose (Alces alces) or white-tailed deer (Odocoileus virginianus). Elk (Cervus elaphus) are social ungulates and the main prey item of wolves (Canis lupus) in Banff National Park (BNP), Alberta. Grouping behaviour may affect the functional response of predators by changing how predators encounter and kill prey. We studied wolf predation on elk in BNP during the winters of 1997-1998 and 1998-1999 and tested how elk group size a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
124
2
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(132 citation statements)
references
References 60 publications
(78 reference statements)
5
124
2
1
Order By: Relevance
“…2). These results are similar to empirical findings of encounter rates between wolves and elk groups where intermediate group sizes of elk had higher encounter rates with wolves than individuals or large groups (Hebblewhite and Pletscher 2002). Together, these results suggest that at small to intermediate group sizes, group detectability effects have a stronger influence on encounter rates than the minimizing effect associated with increasing group size (Ioannou et al 2011).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…2). These results are similar to empirical findings of encounter rates between wolves and elk groups where intermediate group sizes of elk had higher encounter rates with wolves than individuals or large groups (Hebblewhite and Pletscher 2002). Together, these results suggest that at small to intermediate group sizes, group detectability effects have a stronger influence on encounter rates than the minimizing effect associated with increasing group size (Ioannou et al 2011).…”
Section: Discussionsupporting
confidence: 87%
“…access to food; parasite avoidance) may influence social behaviour in animals Ruxton 2002, Beauchamp 2014), here we focus on temporal trade-offs to sociality in terms of predation risk. In certain situations, the dispersion of individuals may be advantageous over group-living: for example, if groups are more detectable than individuals (Hebblewhite and Pletscher 2002;Ioannou and Krause 2008), if aggregation leads to area-restricted search behaviour from predators (Tinbergen et al 1967;Scharf et al 2011) or if the number of individuals predated per encounter is greater than one (Treisman 1975).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of group size and distribution pattern of prey species on encounter rate could have strengthened the selection of <1-year-old boar. Several studies have reported encounter rates to be higher for larger groups of prey (Hebblewhite and Pletscher 2002;Creel and JAJr 2005), probably because of their increased detectability. In the Casentinesi Forests, wild boars live in larger groups than the other ungulate species, particularly the roe deer.…”
Section: Prey Selectionmentioning
confidence: 99%
“…Because female white-tailed deer associate within matrilineal social groups while males tend to be alone or in small groups outside the breeding period (Nixon et al, 1991), these social groups may not change in size with deer density. However, changes in population density or size (Borowski, 2000;Hebblewhite and Pletscher, 2002) may affect the frequency and intensity of interactions among deer within or among social groups (Hirth, 1977;Nixon et al, 1991;Grenier et al, 1999;Kie and Bowyer, 1999).…”
Section: Introductionmentioning
confidence: 99%